Visualizing Smart Tourism Through Smart Community Drivers and Driven Outcomes - Sarmita, Reggy Nelson; Hu, Clark (E-Journal of Tourism, 2024)
The definition and description of smart tourism have mainly focused on implementing ICT in tourism activities. Smart tourism's techno-centric approach threatens to marginalize thriving smart communities, hindering the symbiotic relationship crucial for destination success. In conducting the theoretical and literature review of smart tourism, the authors found that cloud computing, the Internet of Things (IoT), and End-user devices have facilitated the process but have not changed the nature of tourism. Unsustainable tourism practices can overwhelm communities. By fostering collaboration that leverages collective intelligence, technology acceptance, and a system-thinking approach, communities can effectively address the challenges of excessive tourism. This collaborative effort lays the groundwork for a truly smart community that transcends technological advancements